AN ACTIVITY THEORY PERSPECTIVE ON STUDENT-REPORTED CONTRADICTIONS IN INTERNATIONAL TELECOLLABORATION - Olga K. Basharina (Language Learning and Technology, 2007)
This process-oriented study focuses on contradictions that emerged in a WebCT bulletin board collaboration among English learners from Japan, Mexico and Russia, and explains them from the perspective of activity theory (Leont’ev, 1978, 1981; Engeström, 1987, 1999). The study identified a) two intra-cultural contradictions – to post or not to post, to sound formal or informal; b) three inter-cultural contradictions – unequal contribution, genre clash/plagiarism, clash of topic choice; and c) three technology-related contradictions – message overload as hindering community formation, bulletin board as too "slow" when compared to chat, and names and gender confusion. These contradictions were catalyzed by the clash of curricula versus interactive learning paradigms (Lemke, 1998): the outcomes of different cultures-of-use of computer technologies (Thorne, 2003), instructors’ mediation, and resources available to learners within their broader socio-cultural contexts. The study concludes with a discussion of whether the learning paradigms can be bridged and cultures-of-use of computer technologies aligned.